2012
DOI: 10.4067/s0718-221x2012000200008
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de la densidad de plantación inicial en el módulo de elasticidad dinámico de árboles en pie y trozas de una plantación de pino radiata de 28 años, en la zona de arenales, Chile

Abstract: RESUMENEn un ensayo de densidad de plantación inicial (DPI), se evaluó el efecto de cuatro tratamientos (2500, 1667, 833 y 625 árb·ha -1 ) en el módulo de elasticidad dinámico (MOE d ) de Pinus radiata D. Don, de 28 años, creciendo sobre un suelo de la serie Arenales, en la Región del Biobío, Chile.El MOE d se determinó con tecnología acústica utilizando el método de tiempo de vuelo (Tv) para árboles en pie y posterior a su volteo se usó el método de resonancia (Res) para dos trozas de 5 m de longitud (primera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
1
5
1
5
Order By: Relevance
“…The overall strong trend between stress-wave velocity (assumed to be only estimating the stiffness of the outerwood) and stand density implies a solid relationship between the latter and timber stiffness, in line with results from other studies (Lasserre et al 2005;Watt et al 2010). The current results, however, do not support the findings from another study in New Zealand (Grabianowski et al 2004) or the results from a mature spacing study in Chile (Soto et al 2012) which concluded that initial stand density (2500, 1667, 833 and 625 stems ha −1 across four sites) did not influence stress-wave velocity. This raises the possibility that site type may have an influence on silvicultural response.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…The overall strong trend between stress-wave velocity (assumed to be only estimating the stiffness of the outerwood) and stand density implies a solid relationship between the latter and timber stiffness, in line with results from other studies (Lasserre et al 2005;Watt et al 2010). The current results, however, do not support the findings from another study in New Zealand (Grabianowski et al 2004) or the results from a mature spacing study in Chile (Soto et al 2012) which concluded that initial stand density (2500, 1667, 833 and 625 stems ha −1 across four sites) did not influence stress-wave velocity. This raises the possibility that site type may have an influence on silvicultural response.…”
Section: Discussioncontrasting
confidence: 53%
“…In previous radiata pine studies there are conflicting results, with some reporting a strong relationship (Lasserre et al 2005;Watt et al 2011) and others reporting no effect (Grabianowski et al 2004;Soto et al 2012). In this study there was no indication of a strong site effect on this relationship.…”
Section: Discussionmentioning
confidence: 44%
“…In loblolly pine, Clark et al [57] observed an increase in whole-stem SG, MOE, and MOR with an increase in initial planting density, using samples collected from a 21-year-old unthinned spacing study (seven initial spacing levels ranging from 1.8 m × 2.4 m (2244 trees/ha) to 3.6 m × 3.6 m (746 trees/ha) were sampled). Similar improvements in MOE for trees planted at high initial densities were reported in radiata pine [64][65][66][67][68]. The magnitude of the improvement can be large, for example, a 39 percent increase (from 5.4 GPa to 7.5 GPa) was seen in outerwood dynamic MOE (nondestructive test for MOE, MOE dyn ) for 17-year-old radiata pine, as planting density increased from 209 stems/ha to 2551 stems/ha [64].…”
Section: Planting Densitysupporting
confidence: 59%
“…Este método utilizado para medir la velocidad de la onda acústica se denomina "Tiempo de vuelo", y ha sido utilizado por varios autores (Lasserre et al 2005, Lasserre et al 2007, Soto et al 2012).…”
Section: Velocidad De La Onda Acústica En áRboles En Pieunclassified